DUNIA DALAM GENGGAMAN: Ketergantungan manusia pada teknologi komunikasi dalam bentuk visual fotografi ekspresi - Arya Putra, I Putu Dudyk (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
ABSTRACT The development of communication and telecommunications technology in this century has engulfed space and time. Through the development of various forms of communication and information technology in this modern era that are immediate, fast and virtual, interaction (face to face) is now taken over by interactive, a relations that are connected with the media (such as television, telephone, handphone, internet).Humans have evolved with the tools of their creation by facilitating all access to life by pressing sophisticated tools in their hands. Capturing the phenomenon of human dependence on communication technology is a way for photographic artists to translate ideas and imagination into expressions of photographic work which will later not be a solution to answer phenomena, but become a means of criticism in facing this modern age.